The advertisement call of Physalaemus ephippifer (Anura: Leiuperidae) from Brazilian Amazonia - Kaefer, Igor L.; Erdtmann, Luciana K.; Lima, Albertina P. (Zootaxa, 2011)
Physalaemus is recognized as an important system for the study of mechanisms and evolution of animal communication, especially because of studies involving the P. pustulosus species group. Physalaemus ephippifer is considered, together with P. fischeri (enesefae) and an undescribed species, to be the most similar species to the P. pustulosus group in external morphology, osteology, and characteristics of the call. Because of this, P. ephippifer has been included as an outgroup in studies to interpret patterns of signal-receiver evolution in the genus. Whereas details of the advertisement call structure of P. fischeri have been described (Tárano 2001), information (e.g., detailed graphic representation and range of variation) on P. ephippifer calls remains unavailable.